2022
DOI: 10.3389/pore.2022.1610445
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Brentuximab Vedotin Associated Acute Pancreatitis in a Pediatric Hodgkin Lymphoma Patient: Case Report and Literature Review

Abstract: Brentuximab vedotin is a conjugate drug used mainly in Hodgkin lymphoma, systemic and primary cutaneous anaplastic large cell lymphomas, and CD30-expressing peripheral T-cell lymphoma. We report a unique case of acute pancreatitis associated with brentuximab vedotin in a 17-year-old male patient suffering from classical Hodgkin lymphoma. Diagnosed in 2020, the patient was classified to an intermediate therapeutic group and disease’s grade was IIIAE. The patient was treated with brentuximab vedotin and bendamus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Since it is rare for drugs to induce AP, it has been a challenge to identify a particular medication as the cause of this condition. Numerous cases of AP linked to the use of antineoplastic (Engel et al, 2013;Chou et al, 2016;Truszkowska et al, 2022), immunosuppressive (Fontana and Cappelli, 2016;Ding et al, 2022), antiviral (Khadka et al, 2022), anti-hypertensive (Carnovale et al, 2003;Thumma et al, 2019), antidiabetic (Lee et al, 2014;Verma, 2016;Yang et al, 2016), antibacterial (Hung et al, 2009;Jiménez Moreno et al, 2020), and glucocorticoid (Yahiaoui et al, 2017;Wang-Liang et al, 2022) drugs have been reported to date. However, the evidence for an association between these drugs and AP remains weak, and there is a risk of false positives.…”
Section: Discussionmentioning
confidence: 99%
“…Since it is rare for drugs to induce AP, it has been a challenge to identify a particular medication as the cause of this condition. Numerous cases of AP linked to the use of antineoplastic (Engel et al, 2013;Chou et al, 2016;Truszkowska et al, 2022), immunosuppressive (Fontana and Cappelli, 2016;Ding et al, 2022), antiviral (Khadka et al, 2022), anti-hypertensive (Carnovale et al, 2003;Thumma et al, 2019), antidiabetic (Lee et al, 2014;Verma, 2016;Yang et al, 2016), antibacterial (Hung et al, 2009;Jiménez Moreno et al, 2020), and glucocorticoid (Yahiaoui et al, 2017;Wang-Liang et al, 2022) drugs have been reported to date. However, the evidence for an association between these drugs and AP remains weak, and there is a risk of false positives.…”
Section: Discussionmentioning
confidence: 99%